THE ROLE OF EMPLOYEE EMPOWERMENT IN IMPROVING EMPLOYEE PERFORMANCE AT SHANGHAI “JESSIVAR” KIAWA PEANUT FACTORY - Henry Longkutoy; S. L. H. V. Joyce Lapian; Ferdinand Tumewu (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
The success of company management is primarily determined by utilizing human resources, where company managers must pay attention to employees' attitudes, behaviour, desires and needs to encourage employees to improve their performance. The final project aims to determine the observation of employee empowerment at Shanghai "Jessivar" Kiawa Peanut Factory. Khan's theory contains several indicators: Desire, Trust, Confidence, Credibility, Accountability, and Communication. The research method used is qualitative. The analysis technique uses observation, interviews, and documentation. The results of the study found that desire for Shanghai "Jessivar" Kiawa Peanut Factory has been well empowered, trust in Shanghai "Jessivar" Kiawa Peanut Factory can be said to be enough empowered, confident employees at Shanghai "Jessivar" Kiawa Peanut Factory have been well empowered, confident employees at Shanghai "Jessivar" Kiawa Peanut Factory have been well empowered, credibility in Shanghai "Jessivar" Kiawa Peanut Factory has been well empowered, accountability at Shanghai "Jessivar" Kiawa Peanut Factory is quite well empowered, communication in Shanghai "Jessivar" Kiawa Peanut Factory has been well empowered.   Keywords: employee empowerment, employee performance